TRADISI PEMINANGAN DAN WALĪMAT AL-‘URS MASYARAKAT MUSLIM SUKU MARIND PAPUA KABUPATEN MERAUKE PERSPEKTIF AKULTURASI BUDAYA - Amri Gede (Tahkim (Jurnal Peradaban dan Hukum Islam), 2020)
Culture of Marind Tribe in Papua has been preserved for a long time to this day. For example, tradition of marriage proposal and the wedding ceremony. Marind people believe in Islam as a religion for them. Therefore, there is an acculturation process in presenting the practice of the tradition. This study examined the tradition of marriage proposal and walīmat al-'urs of the Marind Muslim society in an overview of cultural acculturation. Qualitative research was used during the research process. In-depth observation and interview were applied during data collection. This study showed that the Marind Muslim people still use the old way of respecting the tradition and minority of Muslim in the family, the execution of mixed-cultured traditions between the two cultures, and the elimination of tradition. While the occurrence of the process of cultural acculturation experienced by the Marind people against the tradition of marriage proposal and wedding ceremony. Therefore, a new tradition in Marind Muslim people has arisen. The result also showed that the Marind Muslim people adhere to the traditions that prioritize the appreciation and practice with the content of the value of the traditional culture. However, on the other hand, it also fulfills all matters pertaining to the Shari'a in Islamic culture. The occurrence of cultural contact between Marind tradition and religion, according to this study, it did not indicate a process of rejection. Keyword:  Marriage Proposal, Walīmat al-'urs (Wedding Ceremony), Marind Tribe, Cultural Acculturation.